Evolution of health system Peru: Good practices and challenges in construction. Decade 2005-2014 - Cañizares Fuentes, W. Ricardo (2018)
Introduction: The improvement of national health systems is a global concern and is part of the discussions in the current international political agenda. In the past years, most south american countries have made efforts to improve their systems introducing reforms and public policies to reach universal access to health care for all citizens. It is necessary to study them, as recommended by the World Health Organization. According to it, this present work studies the evolution of the health system in Peru over a period of 10 years aiming to extract lessons for improvement as well as to provide inputs for other countries. Objectives: To analyze the evolution, good practices and variables influencing the functioning of the health system in Peru. Participants: Former ministers and deputy ministers of health, PAHO representatives, academics, technical experts and representatives of civil society. Methods: Quality approach research, interviews that were recorded, transcribed and coded to identify and analyze the main social representations interviewers had regarding the health system. Results: Increasing funding did not result in increasing access of population to health care, the rectory of Health Ministry was slightly strengthened, and lack of access to comprehensive care and quality, interviewers are in favor of creating a single national financing fund and one health plan for all Peruvians. Conclusions: The rectory has not been strengthening enough. Financial coverage has been improved although the access to health care services has not, and there are consistent gaps in human resources, infrastructure, equipment and access to medicines, in addition to organizational inefficiency.